Juridical Review of Digisexual Activities in Limited Cyberspace: Reviewed from Positive Law in Indonesia - Novia Indah Prasetyowati; Danang Sugihardana; Muhammad Johansyah Maulana; Feri Budi Lestanto; Sekar Diah Ayu Almira; R Rizka (Proceeding International Conference Restructuring and Transforming Law, 2024)
The advancement of technology has resulted in various products to fulfill human sexual needs, ranging from sex toys, sex dolls, to vibrators. However, not only that, technology has also spurred the emergence of various dating applications catering to diverse sexual orientations through smartphones. This research also highlights the importance of public education, law enforcement, regulation, collaboration with the technology industry, further research, and support for victims. Practical implications and policy recommendations are presented to assist society in protecting themselves from the risks and negative impacts of digital sexual practices in the digital era. This study employs a legal approach focusing on norms and literature research methods to analyze the focal aspects of the research. The normative legal approach is utilized to analyze and comprehend all legal regulations related to the research topic. In Indonesia, the regulation of these activities from a positive legal perspective is still under development, largely due to the unique characteristics of digital media and its rapid evolution. The social impacts arising from digisexual activities entail fundamental changes in how individuals interact and experience sexuality. The absence of explicit regulations addressing digisexuality poses a significant challenge within the legal framework in Indonesia. The phenomenon of digisexuality, closely linked with the use of digital technology in the realm of sexuality, has yet to receive specific regulatory treatment at the national level.